Artificial neural network modeling for the prediction of surface area - Abd. Razak, Norhuda (2004)
to provide a platform for discussions on solid state science and technology in all aspects of physical and chemical properties, preparation and characterization techniques, optical properties; macro-, micro- and nano-structures.